The Role of Talent Management Practices in Promoting the Creative Behavior: A Field Study on the Employees of the Saudi Electricity Company in Asir - Al Shumaylah, Turki Aziz Abdullah; Shuaibi, Faisal Ahmed Abed (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to identify the role of talent management practices with the following various dimensions (attracting talent, selecting talent, developing and developing talent, retaining talent) in enhancing creative behavior (sensitivity to problems, fluency, flexibility) from the point of view of employees of the Saudi Electricity Company in Asir. The study used the descriptive analytical approach due to its suitability to the nature of the study, and the questionnaire as the main tool for collecting data from the study sample, which is represented by all (200) employees of the Human Resources Department at the Saudi Electricity Company in Asir. After distributing the questionnaire, (160) were recovered. The data of this study were analyzed using the SPSS statistical package program. Among the most important results of the study: One of the most important practices of attracting talent was the company’s use of many means to advertise job vacancies to attract the best talented people. The study revealed that the practices of retaining talent through an interest in preventing the leakage of talented and creative people from it, and the company’s monitoring of working conditions to suit the requirements of the characteristics There is a statistically significant relationship at a level between talent management practices represented in (attracting talent, selecting talent, developing and developing talent, retaining talent) And between the promotion of creative behavior from the point of view of the employees of the Saudi Electricity Company in Aseer. In light of the results reached, the researcher presents a set of recommendations. Paying attention to analyzing and describing jobs in a way that is commensurate with the internal and external environment, in order to determine the nature and responsibilities of each job and the conditions that must be available in its occupants, setting criteria for measuring talents to enhance all recruitment, selection and appointment processes, presenting methodologies Modern training for development and qualification, as well as formulating a talent development strategy based on an analysis of the internal and external environment.